Fiscal Policies in Economies in Transition - Tanzi, Vito. (Washington, D.C. : International Monetary Fund, 1992)
The collapse of central economic planning in many countries and the breakup of the Soviet Union have put into disarray systems of government revenues and expenditures in those countries. This collection of 16 papers, edited by Vito Tanzi, analyzes the strengths and weaknesses of fiscal policies under the old system of central planning and suggests ways to revitalize those policies in the newly emerging market economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet